To be or not to be a facilitator of reflective learning for medical students? a case study of medical teachers' perceptions of introducing a reflective writing exercise to an undergraduate curriculum. Issue 1 (December 2016) - Sukhato, Kanokporn; Sumrithe, Sutida; Wongrathanandha, Chathaya; Hathirat, Saipin; Leelapattana, Wajana; Dellow, Alan
Abstract Background Introducing reflective writing to a medical curriculum requires the acceptance and participation of teachers. The purpose of this study was to explore medical teachers' views on the benefits of introducing a reflective writing exercise into an undergraduate medical curriculum, including their levels of satisfaction and their concerns. We also investigated effects on the teachers' personal and professional development arising from their roles as novice facilitators. Methods A qualitative approach was employed using semi-structured interviews. During an attachment to Primary Care Medicine course, fourth-year medical students (n = 180) in the Faculty of Medicine, Ramathibodi Hospital, Bangkok, Thailand were assigned to write a reflective essay titled, "A Significant Event in My First Clinical Year". After reading the essays and facilitating between one to three small group discussions based on these, each of the 18 teachers enrolled in our study completed an in-depth face to face interview. Transcripts of these were studied, using thematic content analysis to identify emerging themes. Results The novice facilitators felt that facilitated reflection was both valuable and appropriate for students. They also perceived that it had a positive impact on their own personal and professional lives. In the early phase of implementing this activity, teachers expressed concerns about 1) their ability and confidence as facilitators in small group discussion 2) their ability to deal with emotions raised within their groups 3) the effectiveness of the activity 4) poor presentation and possible fabrication of student work. Conclusions Most teachers regarded this activity as being beneficial to them, to student learning, and to the curriculum. Their insights, including concerns about the level of skill needed for facilitation, provide valuable material for planning a comprehensive faculty development programme.